Trophic ecology and metabolism of two species of nonnative freshwater stingray (Chondrichthyes: Potamotrygonidae) - Pagliarini, Cibele Diogo [UNESP] (2020)
The stingrays Potamotrygon amandae and Potamotrygon falkneri are nonnative species established in the Upper Paraná basin. Although they are widely distributed, few studies on their diets or respective metabolic responses exist. Therefore, the aim was to evaluate the dietary composition, trophic niche breadth and lipid/protein concentrations in muscle and hepatic tissues of these two species, as well as the interrelationships between them. The individuals were collected in two areas on the Upper Paraná River. The stomachs and samples of muscle and liver tissues were taken for analysis. A broad dietary spectrum was observed for both species, along with differences in dietary composition, with a higher consumption of detritus by P. amandae and Baetidae by P. falkneri. No differences were observed in the trophic niche breadth. Regarding the metabolic variables, differences were only found in the hepatic protein, with a higher content observed in P. falkneri. A significant positive correlation was observed between items of animal origin and detritus with muscle protein for this species. This shows that such feeding habits, which are characteristic of a generalist, influenced the metabolism of the species and possibly contributed to the successful adjustment of the species to new habitats in the Upper Paraná River.